The Pact of Baghdad on Account of its Effect to Relationship of Turkish - Arabian - Mustafa Bostancı (Gazi Akademik Bakış)
The base of Baghdad Pact, which was organized for the purposes of preventing penetration of the Soviet Union into Middle East, was laid by a convention entered by and between Turkey and Iraq on February 24, 1955, and Iran, Pakistan and England joined the pact at a later date. Effects of Baghdad Pact, which alienated Turkey from the region while reinforcing anti-western camp, on Arabian society were not positive at all; particularly Egypt protested against this pact accepting it to be the heaviest strike on Arabian Union. No Arabian state other than Iraq has taken part in this convention, which is kept open to member states of Arabian Union as well as governments of Middle East wishing to create cooperation. Iraq Government officially announced its secession from Baghdad Pact in 1959 upon the military coup of General Kasım, which was replaced by a new convention including the USA with the new center in Ankara. The name of pact was changed to be Central Treaty Organization (CENTO). Organization completed its historical mission after Iran’s Islamic Revolution in 1979.